2014
DOI: 10.17338/trainology.3.1_31
|View full text |Cite
|
Sign up to set email alerts
|

Primum non nocere: A commentary on avoidable injuries and safe resistance training techniques

Abstract: Objectives:Recently attention has been brought to potentially unsafe training methods within the practice of resistance training. Thus purpose of this commentary is to highlight the importance of the moral injunction Primum non nocere, and of weighing risks to rewards of training methods, for those providing resistance training recommendations and practitioners of it as a training approach. Design & Methods: Narrative reviewResults: It appears that many popular resistance training methods that make use of eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
0
6
0
1
Order By: Relevance
“…13 However, whilst isometric knee extensor training may be less effective than plyometric training for increasing CMJ, isometric training is evidently an approach that may still benefit jump performance and some have argued that explosive training (such as plyometrics) may represent an unnecessary injury risk. 14,15 Potential mechanisms for improved CMJ may include increased tendon stiffness and rate of force development. 16 Fast onset of activation of the leg muscles is beneficial for CMJ as this increases impulse and consequently, jump height.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 However, whilst isometric knee extensor training may be less effective than plyometric training for increasing CMJ, isometric training is evidently an approach that may still benefit jump performance and some have argued that explosive training (such as plyometrics) may represent an unnecessary injury risk. 14,15 Potential mechanisms for improved CMJ may include increased tendon stiffness and rate of force development. 16 Fast onset of activation of the leg muscles is beneficial for CMJ as this increases impulse and consequently, jump height.…”
Section: Discussionmentioning
confidence: 99%
“…leading up to an important cup match) for fear of potentially increased injury risk. 14,15 In female populations, this may be particularly important due to their increased injury risk. 8 No significant changes were observed in either group for SS, ZS, SSB, or ZSB.…”
Section: Discussionmentioning
confidence: 99%
“…Though an appreciable concern, and a rationale for the present study, is that people might engage in training practices that are unnecessary and/or potentially harmful due to increased injury risks (Fisher et al, 2014), there may be other unintended consequences of using media imagery to change training practices towards the 'evidence based' recommendations. Our results suggested that 'evidence based RT recommendations' text alongside a hyper-muscular physique might influence beliefs regarding training practices.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent study suggested that males engaged in CrossFit style resistance training (RT) using free weight type exercises were less likely to report health-based motivations for exercise compared to a personal training group performing predominantly supervised machine based RT (Fisher, Sales, Carlson & Steele, 2016). Yet, attaining cosmetic or performance outcomes through the approach typified by what could be termed the 'lift big-get big' culture (heavy free weight resistance exercises, often argued as more 'functional'), could represent an increased risk of injury (Fisher, Steele, Brzycki & DeSimone, 2014). Despite this there is an increasing interest worldwide in such RT approaches (Thompson, 2017;Thompson, 2018), and a growing group of male gym users.…”
Section: Introductionmentioning
confidence: 99%
“…In an aging population with only 10–15% of persons over 55 years of age performing any strengthening activities [ 36 ] it is important to consider time-efficient methods which might encourage exercise adherence. The present authors have previously recommended single sets of an exercise, performed infrequently (1-2×/week), to a high intensity of effort, using resistance machines through a full range of motion, at a repetition duration that maintains muscular tension as being optimal for increasing strength whilst efficiently using time and minimising risk of injury [ 6 , 37 ].…”
Section: Introductionmentioning
confidence: 99%